Dynamic contrast-enhanced MRI of ocular melanoma. Issue 2 (April 2015) - Jiang, Xuyuan; Asbach, Patrick; Willerding, Gregor; Dulce, Miriam; Xu, Ke; Taupitz, Matthias; Hamm, Bernd; Erb-Eigner, Katharina
Abstract : Dynamic contrast-enhanced MRI is used for the assessment of microvasculature in several tumours. We aimed to assess the contrast signal enhancement characteristics of ocular melanoma. Forty patients with ocular melanoma were prospectively investigated with ocular MRI including dynamic contrast-enhanced sequences over a 13-month period. A region-of-interest analysis of the images was carried out to calculate signal enhancement characteristics after a contrast injection. Clinical follow-up data such as extraocular spread and development of liver metastasis were compared with the signal enhancement characteristics of the ocular melanoma. In 39 patients (98%), the ocular melanomas showed an early strong signal enhancement after contrast injection, resulting in a mean time of maximum enhancement of 49 s. Clinical follow-up was available in 28 patients (70%) and indicated that the peak signal intensity was significantly increased ( P =0.039) in patients who developed extraocular spread or liver metastasis at a later stage. Ocular melanoma shows signal enhancement characteristics of hypervascular neoplasms. This study provides baseline curve pattern data that may be useful for assessing changes in vascularity, for example during therapy response. Furthermore, the study showed that a strong signal enhancement of the ocular melanoma might be linked to a less favourable prognosis.